The two governments Alfonso Lopez: state and economic and social reforms in Colombia (1934-1938, 1942-1945) (2013)
This article briefly reviews the reformist intentions of one of the major governments in Colombia during the twentieth century, that of Alfonso Lopez. For this purpose, consider specifically, the main background, the general context of the two governments included from 1934 to 1938 and 1942 to 1945, economic and social reforms attempted to carry out and, finally, a brief interpretation of these reforms in the context of this historic moment.